Care to terminal patients. Perception of nurses from the intensive care unit of a hospital - Tamaki, Camila Mussolin [UNESP]; Meneguin, Silmara [UNESP]; Alencar, Rubia Aguiar [UNESP]; Luppi, Claudia Helena Bronzatto [UNESP] (Investigación Y Educación En Enfermería, 2014)
Objective. To identify the perception of nurses with regard to the process of providing care to patients in the context of hospice care. Method. Qualitative study using the methodological framework Collective Subject Discourse. A total of 18 nursing professionals of the adult intensive care unit of a public hospital in São Paulo, Brazil were interviewed between June and August 2012. Results. The process of providing care to terminal patients is permeated by negative, conflictive and mixed feelings. As regards communication, while the participants acknowledge its importance as a therapeutic resource, they also admit a lack of professional qualification. Conclusion. The interviewees have difficulties to deal with care provided to terminal patients. The qualification of these professionals needs to be improved, starting in the undergraduate program.

Objetivo. Identificar la percepción de los enfermeros sobre el proceso del cuidado de pacientes en el contexto de la asistencia paliativa. Metodología. Estudio cualitativo que utilizó el referencial metodológico del Discurso del Sujeto Colectivo. Fueron entrevistados 18 profesionales de enfermería en una unidad de terapia intensiva adulta de un hospital público de Sao Paulo, Brasil, entre junio y agosto del 2012. Resultados. El proceso de cuidar de un paciente sin posibilidades de curación es permeado por sentimientos negativos, conflictivos e incongruentes. Con relación a la comunicación admiten la falta de preparación profesional, aunque reconocen su importancia como recurso terapéutico. Conclusión. Los enfermeros tienen dificultades con el cuidado del paciente terminal. Es necesario reforzar su preparación desde la formación de pregrado.

Objetivo: identificar a percepção dos enfermeiros sobre o processo de cuidar de pacientes no contexto da assistência paliativa. Metodologia: Estudo qualitativo que utilizou o referencial metodológico do Discurso do Sujeito Coletivo. Foram entrevistados 18 profissionais de enfermagem, em uma unidade de terapia intensiva adulta de um hospital público de São Paulo, Brasil, entre junho e agosto de 2012. Resultados: O processo de cuidar de um paciente sem possibilidades de cura é permeado por sentimentos negativos, conflitantes e incongruentes. Com relação à comunicação, há o reconhecimento de sua importância, até mesmo como recurso terapêutico, embora admitam o despreparo profissional. Conclusão: Os enfermeiros têm dificuldades no cuidado ao paciente terminal. Deve-se reforçar a preparação desses profissionais desde a graduação.
Cuidar a pacientes terminales. Percepción de los enfermeros de una unidad de terapia intensiva de un hospital público
Cuidar de pacientes terminais. Percepção dos enfermeiros de uma unidade de terapia intensiva de hospital público
Keywords: Palliative care; Communication; Intensive care units; Nursing; Cuidados paliativos; Comunicación; Unidades de terapia intensivos; Enfermería; Cuidados paliativos; Comunicação; Unidades de terapia intensiva; Enfermagem